2023
DOI: 10.3390/agriculture13030724
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Auxin and Cytokinin on the Growth and Development of Selected Crops

Abstract: With a very diverse structure and small molecules, phytohormones are regulators of plant growth and development. Despite the fact that they are synthesized by plants in small quantities, they are highly active physiologically. According to their action, phytohormones can be divided into two categories, as either activators of plant growth and development or as inhibitors, with auxins and cytokinins belonging to the former group. Auxins are synthesized by plants in the apical meristems of shoots, but also in yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 102 publications
2
35
0
Order By: Relevance
“…[7], compared with other cytokinins. Furthermore, a recent study also reported that combining cytokinins and auxins stimulated the elongation of shoots and yielded a more significant shoot number, shoot length, and fresh weight of several crops, including Philodendron bipinnatifidum, than treatments with cytokinins alone [16,22]. Thus, the effect of cytokinin (BAP) and auxin (NAA) at different concentrations on the shoot prolifera-tion of Philodendron erubescens pink princess was investigated in this study.…”
Section: Effect Of Pgrs On Shoot Proliferationmentioning
confidence: 91%
See 3 more Smart Citations
“…[7], compared with other cytokinins. Furthermore, a recent study also reported that combining cytokinins and auxins stimulated the elongation of shoots and yielded a more significant shoot number, shoot length, and fresh weight of several crops, including Philodendron bipinnatifidum, than treatments with cytokinins alone [16,22]. Thus, the effect of cytokinin (BAP) and auxin (NAA) at different concentrations on the shoot prolifera-tion of Philodendron erubescens pink princess was investigated in this study.…”
Section: Effect Of Pgrs On Shoot Proliferationmentioning
confidence: 91%
“…Generally, NAA, a member of the auxin family, plays an essential role in plant cell growth, differentiation, and development, specifically the formation of roots [24,25]. Although auxins have been reported to stimulate shoot elongation [22], the application of NAA alone did not significantly improve the shoot formation of Philodendron pink princess compared to the control without the supplementation of PGRs (Treatment 1). Considering the combinations of BAP and NAA, these treatments did not exert a synergistic effect on shoot proliferation compared with treatment using BAP at 1.0 mg/L alone.…”
Section: Effect Of Pgrs On Shoot Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because tryptophan, even if exogenously supplied, increases the tissue levels of auxin in soybeans. Auxins belong to the class of hormones activating plant growth and development [49], directly affecting cell division, elongation, and differentiation [50]. There is clear evidence that these hormones induce H + ion excretion and consequent tissue elongation of soybean hypocotyls [51].…”
Section: Exogenous Tryptophan Improved Seed Germination Fitness and S...mentioning
confidence: 99%